WORKSHOP PENINGKATAN KOMPETENSI GURU SEKOLAH DASAR MELALUI KEGIATAN MERDEKA BELAJAR - Nurrohmatul Amaliyah; Supriansyah Supriansyah; Puri Pramudiani; Moch. Muslim ahbub S; Dama Putri Prawito; Luthfi Khoirunnisa (Jurnal Visi Pengabdian Kepada Masyarakat, 2023)
The independent learning policy is a step towards transforming education for the realization of superior Indonesian Human Resources (HR) who have a Pancasila Student Profile. One of the episodes of Freedom of Learning is the realization of four main programs of the Freedom of Learning policy, namely: National Standardized School Examination (USBN), National Examination (UN), Learning Implementation Plan (RPP) and New Student Admission Regulations (PPDB). In improving one of the teacher's competencies, namely increasing professionalism, it is necessary to carry out activities in the form of workshops related to the mastery of the learning material taught, including the structure of the lesson, the concept of the lesson and the scientific mindset of the material. One of the things experienced by teachers in elementary schools is the development of learning tools so as to produce a Pancasila Student Profile in accordance with the directions contained in the Merdeka Curriculum. This activity was carried out in the form of a workshop which took place at SDN Pinangsia 06 Pagi, West Jakarta.